DETERMINANT FACTORS INFLUENCING HOUSING AFFORDABILITY AMONG BUMIPUTERA YOUTHS IN KLANG - Sukereman, Anis Syazwani; Rosman, Siti Hasniza; Ismail, Suhana; Raja Faisal, Raja Faris; Berahim, Nur (PLANNING MALAYSIA, 2021)
Housing affordability issues arise when the household income is insufficient to cover the expenses of owning a house due to high housing market prices. This significantly impacts potential buyers, especially members of the youth generation who have just embarked on their careers. This study contributes to the empirical studies related to the monetary and non-monetary factors that influence the affordability of housing for Bumiputera youths in Klang. Primary data was gathered from 382 respondents using purposive stratified sampling. The findings indicate that seven main factors strongly influence housing affordability for Bumiputera youths: household income, housing price, loan approval, household expenditure, type of property, number of working households and location. Thus, the findings of this study will contribute to policy decisions, assessments and practices related to housing affordability among Bumiputera youths and support the implementation of the government policy to ensure that at least 75% of Bumiputera households are able to own residential property.